Fuentes científicas en la obra del humanista Bernardino Gómez Miedes - Ramos Maldonado, Sandra Inés (Minerva: Revista de filología clásica, 1998)
Prosopographic analysis of a book, the Commentariorum de sale libri V, which, without being strictly scientific, approaches multiple fields of science from a philosophical and religious perspective. It mainly deals with natural history, which becomes evident by the fact that Pliny is the author's most quoted source after the Bible. The sources of the second scientific book by Gómez Miedes are also analysed, the Manual contra la gota, which on this occasion is written in vernacular, in order to link and compare the two works.